Pengaruh Penerapan Model Inkuiri Terbimbing Terhadap Keterampilan Proses Sains dan Hasil Belajar Siswa - Anna Juniar; Pravil Mistryanto; Niru Sapla; Dewi Dewi (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2019)
This study aims to find out: 1) whether the increase in student learning outcomes taught by the Guided Inquiry model is higher than the increase in student learning outcomes taught by Conventional models; 2) whether the increase in the Science Process Skill (SPS)  of students who are taught with the Guided Inquiry model is higher than the increase in the student's SPS that is taught with Conventional models; 3) is there a significant correlation between learning outcomes and student SPS through the application of Guided Inquiry model. The population of this study is all students of class XI MIA 1 Binjai Public High School and Binjai 5 Public High School year 2017/1018. Samples were taken using purposive sampling technique as many as two classes. The test instrument used is 40 multiple choice questions (cognitive), 10 essay questions (SPS). The non-test instruments used were observation sheets (affective, psychomotor) and questionnaire sheets. Based on the results of the study it can be concluded that there is an increase in learning outcomes, science process skills and there is a significant correlation in students who are taught by using the Guided Inquiry model higher than the increase in student learning outcomes using Conventional models.